Drug reaction with eosinophilia and systemic symptoms (DRESS syndrome) – case report - Okruszko, Anna; Baran, Anna; Zwierz-Gugała, Dorota; Chodynicka, Bożena; Flisiak, Iwona (Dermatology Review/Przegląd Dermatologiczny, 2013)
Introduction. Drug reaction with eosinophilia and systemic symptoms (DRESS) is a serious, potentially life-threatening syndrome with skin lesions, fever, internal organ involvement and eosinophilia. Objective . To present the case of a woman with DRESS syndrome after the anticonvulsant drug lamotrigine. Case report. A woman, 25 years old, suffering from epilepsy, was admitted to the hospital after the change of valpromic acid to lamotrigine, which caused generalized maculopapular eruptions and laboratory blood test abnormalities. After withdrawal of the causative drug and treatment with corticosteroids and antihistaminic preparations, skin lesions disappeared and the values of laboratory blood tests improved. Conclusions . Due to the high rate of mortality (10%) in DRESS, a quick diagnosis is of crucial value. Most important is a detailed anamnesis, immediate withdrawal of the causative drug, and in severe cases therapy with systemic corticosteroids.